Tunable Multi‐Bit Nonvolatile Memory Based on Ferroelectric Field‐Effect Transistors. (28th December 2021) - Zhang, Qing; Xiong, Hao; Wang, Qiangfei; Xu, Liping; Deng, Menghan; Zhang, Jinzhong; Fuchs, Dirk; Li, Wenwu; Shang, Liyan; Li, Yawei; Hu, Zhigao; Chu, Junhao
Abstract: Ferroelectric field‐effect transistors (FeFETs) with 2D semiconductors as channel materials have been fabricated to achieve miniaturized size, high storage, and low power consumption. The FeFETs are studied based on few‐layer MoS2 sheets on the non‐lead Bi0.85 La0.15 Fe0.92 Mn0.08 O3 (BLFMO) ferroelectric films with a large remnant polarization ( P r  ≈ 36 μC cm −2 ). In FeFETs, the conductivity states of the 2D semiconductor can be tuned by the ferroelectric polarization. It is found that the MoS2 ‐based FeFETs display a large memory windows exceeding 25 V, a high on/off ratio (> 10 5 ), remarkable program/erase ratio (≈ 10 4 ), competitive retention, endurance, and high‐speed performance. Moreover, the 2D based FeFETs exhibit switchable multi‐bit data storage by applying different amplitudes of negative gate voltage pulses to enhance the data storage density. On the basis of these characteristics, the 2D‐FeFETs are potentially able to meet the need for scalability, capacity, retention, and endurance of nonvolatile memory. Abstract : Using 2D MoS2 sheets as the channel semiconductor and (La, Mn)‐codoped BiFeO3 films as the ferroelectric dielectric, N‐type field‐effect transistors are successfully achieved and exhibit a large memory windows exceeding 25 V, a high on/off ratio about 10 5, and an obvious multi‐bit memory effect.